2017
DOI: 10.5005/jp-journals-10051-0084
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Apically Extruded Debris of Different Single File Systems: WaveOne Gold, One Shape, F360, and Reciproc: An in vitro Study

Abstract: dimensional obturation. During the process, the debris of the root canal system is pushed out from the canals, leading to treatment failure and flare-ups. 1 Many factors contribute to debris extrusion. According, 2 irrigation of the root canal space during instrumentation is one of the factors that led to an increased amount of debris extrusion. Teeth with necrotic pulp permitted more irrigant extrusion compared with vital teeth. The depth of file insertion into the root canal is another factor affecting debri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…The results of the current study were in similar to the results of Bürklein et al (2012) (26) Surakanti et al (2014) (10) and Uzun et al (2016) (29) who reported that, the use of the reciprocating single-file system was associated with more debris extrusion than the full-sequence multi-file rotary system.Also,these elucidations were consistent with the three-Dimensional Micro-computed Tomography outcomes reported by Robinson et al (2013) (25) .On the contrary, the findings of the current study disagree with those obtained byAbou El Nasr & Gawdat (2017) (27) and Tomer et al (2017) (28) who reported that, the reciprocating single-file system "WaveOne Gold" out performed the rotary system "OneShape" instruments with less apically extruded debris.…”
Section: Groups Apically Extruded Debris (G)supporting
confidence: 85%
“…The results of the current study were in similar to the results of Bürklein et al (2012) (26) Surakanti et al (2014) (10) and Uzun et al (2016) (29) who reported that, the use of the reciprocating single-file system was associated with more debris extrusion than the full-sequence multi-file rotary system.Also,these elucidations were consistent with the three-Dimensional Micro-computed Tomography outcomes reported by Robinson et al (2013) (25) .On the contrary, the findings of the current study disagree with those obtained byAbou El Nasr & Gawdat (2017) (27) and Tomer et al (2017) (28) who reported that, the reciprocating single-file system "WaveOne Gold" out performed the rotary system "OneShape" instruments with less apically extruded debris.…”
Section: Groups Apically Extruded Debris (G)supporting
confidence: 85%
“…These results were in agreement with a recent study which revealed that, maximum amount of debris extruded by Reciproc while Wave One Gold system resulted in smallest quantity of debris extrusion in comparison with WaveOne Gold, One Shape and F360 file systems (27) .…”
Section: Discussionsupporting
confidence: 93%
“…These results were inconsistent with other study which detected that smallest quantity of periapical debris extrusion was resulted by Wave One Gold, while maximum amount of debris was resulted by Reciproc, when compared with Wave One Gold, One Shape and F360 file systems. This divergence in results could be explained by using different teeth (straight single canals) (27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Reciprocating single-file systems extrude fewer bacteria apically than the conventional multifile rotary system[ 16 ] In WOG, each file has a fixed taper from D1–D3, and a progressively decreasing taper from D4–D16, which serves to preserve dentin and also provides space for more debris to auger out[ 20 ] PTN X1 has a square cross-section in the last 3-mm segment and lacks offset design, thus more chances of debris extrusion[ 24 ] WOG is a single-file system unlike PTN; requiring minimum instrumentation and hence less extrusion of debris. [ 25 ] …”
Section: Discussionmentioning
confidence: 99%